2009
DOI: 10.2174/1874076600903010014
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Application of Botulinum Toxin in Clinical Practice

Abstract: Botulinum toxin, one of the most potent toxins known, is produced by Clostridium botulinum. It causes a temporary paralysis of muscles by inhibiting vesicular release of acetylcholine in neuromuscular junction and synaptic transmission at cholinergic nerve terminals and causes a temporary paralysis of muscles. Since the approval of botulinum toxin A by FDA for strabismus and blepharospasm in 1989 and botulinum toxin B for cervical dystonia in 2000, its therapeutic uses are expanding. To date, both the serotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…By far, the major advantage of peripheral procedures is the repeatability. However, the same may not be applicable to BI, where due to development of antibodies to botulinum the patient may become a non-responder to repeated injections [99]. Further, many authors reported that repeated peripheral procedures may result in high incidence of complications [50,56,57,70].…”
Section: Discussionmentioning
confidence: 99%
“…By far, the major advantage of peripheral procedures is the repeatability. However, the same may not be applicable to BI, where due to development of antibodies to botulinum the patient may become a non-responder to repeated injections [99]. Further, many authors reported that repeated peripheral procedures may result in high incidence of complications [50,56,57,70].…”
Section: Discussionmentioning
confidence: 99%
“…Injection of BoNT has been found to provide relief for writer’s cramp, 60 particularly in those with pronation/flexion pattern. 61 A number of studies have shown improvement in 80% of patients following at least one injection series, with efficacy evident at 1 week and lasting up to 12 weeks. 47 Pain is generally improved more than motor function.…”
Section: Clinical Applications Of Botulinum Toxin In Pediatric Neurolmentioning
confidence: 99%
“…Side effects include hand weakness, mostly mild and transient, and localized pain at the injection site. 61 , 63 …”
Section: Clinical Applications Of Botulinum Toxin In Pediatric Neurolmentioning
confidence: 99%
See 1 more Smart Citation
“…In Bangladesh a large number of patients are suffering from neurological disorders which can be treated by botulinum toxin. The toxin is costly and this leads is a big issue for the application among the patients of this country (Dash and Araf 2009). In National Institute of Neurosciences & Hospital, Dhaka, this therapeutic approach is carried out by a group of well-trained neurologist.…”
mentioning
confidence: 99%